Ara-c induces cell cycle G1/S arrest by inducing upregulation of the INK4 family gene or directly inhibiting the formation of the cell cycle-dependent complex CDK4/cyclin D1. Issue 18 (17th September 2019) - Sun, Fuze; Li, Niannian; Tong, Xiaoling; Zeng, Jie; He, Songzhen; Gai, Tingting; Bai, Yanmin; Liu, Lanlan; Lu, Kunpeng; Shen, Jianghong; Han, Minjin; Lu, Cheng; et al.
ABSTRACT: Cytosine arabinoside (Ara-c) is a pyrimidine anti-metabolite that is capable of interfering with cellular proliferation by inhibiting DNA synthesis. Each inhibitor of cyclin-dependent kinase 4 (INK4) family member has the ability to bind to cyclin-dependent kinase 4 (CDK4) and inhibit the formation of the cell cycle-dependent CDK4/cyclin D1 complex, subsequently leading to cell cycle arrest in the G1/S phase. In this study, the expression of INK4 family genes in kidney cancer and the impact of these genes on patient prognosis were examined. Additionally, the effects of INK4 family genes and Ara-c on cell proliferation and tumor formation and development were examined. Finally, a potential association between Ara-c-induced cell cycle arrest and INK4-associated gene expression was evaluated. An upregulation of INK4 family genes was found to be positively correlated with the prognosis of patients with kidney cancer. Both the INK4 family genes and Ara-c were shown to induce cell cycle arrest and inhibit tumor formation and development. Moreover, Ara-c-induced cell cycle arrest was found to be associated with an Ara-c-induced upregulation of INK4 family gene expression, which ultimately inhibited the formation of the CDK4/cyclin D1 complex. These findings suggested that an upregulation of INK4 family genes has a positive effect on kidney cancer prognosis and can inhibit the formation and development of tumors. Moreover, Ara-c was shown to promote the upregulation of INK4 family genes, at the same time, Ara-c could directly regulate the cell cycle-dependent genes CDK4 and cyclin D1 ( CCND1 ), independent of the INK4 family genes.